2019
DOI: 10.18494/sam.2019.2424
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Effects of Chain Extenders and Cross-linking Agents of Polyurethane Elastomers Using Independent Building Vibration Isolation Sensor

Abstract: Polymeric materials are used for vibration protection owing to their high-energy dissipation or adsorption. In this study, polyurethane elastomers (PUEs) were prepared using six kinds of chain extender and three types of cross-linking agent. The relationships between their structures and vibration isolation performances were investigated in detail using an independent building vibration isolation sensor. The results showed that elastomers with fewer main chain carbon atoms exhibited better vibration isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…A previous study (Gui) 46 shows a similar trend that polyurethane with BDO will exhibit a higher compression modulus because the forming of ordered hard segments are more easily in (Figure 5(c)). For the S_PTD series, there is a higher chain‐extender content so the hard‐segment weight percentage is increased and ordered hard segments are formed.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…A previous study (Gui) 46 shows a similar trend that polyurethane with BDO will exhibit a higher compression modulus because the forming of ordered hard segments are more easily in (Figure 5(c)). For the S_PTD series, there is a higher chain‐extender content so the hard‐segment weight percentage is increased and ordered hard segments are formed.…”
Section: Resultssupporting
confidence: 68%
“…A previous study (Gui) 46 shows a similar trend that polyurethane with BDO will exhibit a higher compression modulus because the forming of ordered hard segments are more easily in (Figure 5(c) series, there is a higher chain-extender content so the hardsegment weight percentage is increased and ordered hard segments are formed. By involving of DMBA ( Figure 5(b)), the W_PTD series show that increasing the number of side chains of the chain extender decreases the compression modulus because there is less micro-phase separation due to the steric hindrance of -COOH from DMBA.…”
Section: Compression and Tensile Test For Wpu-urea And Spu/urea Filmssupporting
confidence: 61%
“…The bands at around 1600 cm −1 can be assigned to the vibration absorption peak of the benzene ring, indicating that the PUE has the presence of benzene ring 36 . The characteristic peak of the CO group is appeared at around 1728 cm −1 , including hydrogen‐bonded CO (1700 cm −1 ) and the free one (1730 cm −1 ) 38–40 . The fitting of the peak area of hydrogen‐bonded CO and the free one can be clearly seen in Figure S1.…”
Section: Resultsmentioning
confidence: 90%
“…36 The characteristic peak of the C O group is appeared at around 1728 cm −1 , including hydrogenbonded C O (1700 cm −1 ) and the free one (1730 cm −1 ). [38][39][40] The fitting of the peak area of hydrogen-bonded C O and the free one can be clearly seen in Figure S1. The hydrogen-bonded carbonyl group only presents in the hard segment and the free carbonyl group only disperses in the soft segment, indicating that the hydrogen bonding amount (HBA) of the carbonyl group represents the degree of microphase separation.…”
Section: Ftir Analysismentioning
confidence: 98%
“…[13,14] Studies have confirmed the positive effect of the polyols side groups and chain extenders on the damping enhancement, which can be attributed to the increase in the friction of the molecular chain. [15][16][17] Jiang et al [18] effectively increased the damping-temperature range by introducing a disulfide bond and a hanging-chain structure. The damping performance was significantly improved by the targeted design of polyurethane molecular structure.…”
Section: Introductionmentioning
confidence: 99%